2014
DOI: 10.1111/1462-2920.12431
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of a consortium between unicellular algae and the N2 fixing cyanobacterium UCYNA in the North Atlantic Ocean

Abstract: Summary The globally abundant, uncultured unicellular cyanobacterium UCYN‐A was recently discovered living in association with a eukaryotic cell closely related to a prymnesiophyte. Here, we established a double CAtalysed Reporter Deposition‐Fluorescence In Situ Hybridization (CARD‐FISH) approach to identify both partners and provided quantitative information on their distribution and abundance across distinct water masses along a transect in the North Atlantic Ocean. The N2 fixation activity coincided with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
34
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 80 publications
(126 reference statements)
11
34
1
1
Order By: Relevance
“…This supports previous observations from the North Pacific (Thompson et al, 2012) and the North Atlantic (Krupke et al, 2014a). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This supports previous observations from the North Pacific (Thompson et al, 2012) and the North Atlantic (Krupke et al, 2014a). …”
Section: Discussionsupporting
confidence: 93%
“…Characterization of the partnership Microscopic observations revealed a population size spectra and phenotype consistent with previous reports, with small prymnesiophyte host cells of 2-3 μm typically with one cyanobacterial UCYN-A1 symbiont (Thompson et al, 2012;Krupke et al, 2014a). On the other hand, the cell size of the UCYN-A2 host in open ocean samples was 4-5 μm, clearly smaller than that described in coastal sites, about 7-10 μm (Hagino et al, 2013;Thompson et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This implies a potential role of phosphate limitation in the shift in diazotroph community composition. UCYN-A1 and γ-24774A11 both appear to be broadly distributed throughout low-nutrient marine waters (Thompson et al, 2014;Langlois et al, 2015), and it has been hypothesised that these taxa thrive in oligotrophic conditions (Church et al, 2008;Krupke et al, 2014). In line with our findings in the ATS and Coral Sea, Moisander et al (2014) recently demonstrated that γ-24774A11 was significantly negatively correlated to soluble reactive phosphorous in the western South Pacific.…”
Section: Arafura Sea Coral Seasupporting
confidence: 88%